2018
DOI: 10.1016/j.ecolecon.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Is Taxing Waste a Waste of Time? Evidence from a Supreme Court Decision

Abstract: A B S T R A C TEnvironmental taxes are often underexploited. This paper analyses the effectiveness of a garbage tax, assessing its effects on multiple outcomes as well as its acceptability. We study how a Supreme Court decision, mandating the Swiss Canton of Vaud to implement a tax on garbage, affects garbage production and beliefs about the tax. We adopt a difference-in-differences approach exploiting that parts of Vaud already implemented a garbage tax before the mandate. Pricing garbage by the bag (PGB) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 35 publications
4
33
0
1
Order By: Relevance
“…More recently, Allers and Hoeben (2010) applied a difference-in-difference approach to control for unobservable local characteristics on a sample of 458 Dutch municipalities and found a significant effect for unit pricing in reducing waste generation and increasing recycling, even after controlling for endogeneity; the price effect depends on the pricing system: weight-based systems reduce waste quantities more than volume-based systems (for compostable waste they estimate an elasticity of -1.77 with respect to weight-based PAYT). Similar evidence was provided more recently by Morlok et al (2017) for Germany and by Carattini et al (2018) for Switzerland.…”
Section: The Advantages Of Unit Pricing: Theory and International Evidencesupporting
confidence: 87%
“…More recently, Allers and Hoeben (2010) applied a difference-in-difference approach to control for unobservable local characteristics on a sample of 458 Dutch municipalities and found a significant effect for unit pricing in reducing waste generation and increasing recycling, even after controlling for endogeneity; the price effect depends on the pricing system: weight-based systems reduce waste quantities more than volume-based systems (for compostable waste they estimate an elasticity of -1.77 with respect to weight-based PAYT). Similar evidence was provided more recently by Morlok et al (2017) for Germany and by Carattini et al (2018) for Switzerland.…”
Section: The Advantages Of Unit Pricing: Theory and International Evidencesupporting
confidence: 87%
“…It is shown that illegal disposal may be an issue in the Netherlands as some early innovators, such as the municipality of Oostzaan, moved back to a flat system due to illegal disposal. By contrast, in the Swiss city of Lausanne, Carattini et al (2018) show that four years after the introduction of a unit-based pricing system, illegal disposal remained a minor issue.…”
Section: Switch_greenmentioning
confidence: 89%
“…Another survey shows that, once the policy was in place, both commuters and noncommuters were less skeptical about it (D. Andersson & Nässén, 2016). Carattini et al (2018) exploited a regulatory change in a region of Switzerland, which enabled them to analyze people's perceptions and acceptance of pricing domestic refuse by the bag before and after the scheme's implementation, and to compare them with a control group composed of people living in municipalities that had already implemented the tax. Their study suggests that residents were willing to pay 70% more for the price of a refuse bag once the policy was implemented than they had been before.…”
Section: The Impact Of Time and Experience On Attitudesmentioning
confidence: 99%